The craft of tonal counterpoint - Benjamin, Thomas (Routledge, 2003)
The Craft of Tonal Counterpoint is an introductory text to the analysis and composition of tonal counterpoint. Using examples from the music of J.S. Bach - the master of this style - the author takes students through a series of carefully graded, cumulative exercises that stress both analysis and writing. Benjamin covers chromaticism and fugal writing in exceptional detail. The exercises cover a wide range of formats, including error detection, linear pitch reduction, analysis and composition. The book also incorporates a 100-page anthology of scores, effective for analysis, in-cla.
Revised edition of: Counterpoint in the style of J.S. Bach. 1986.
"Anthology (all works are by J.S. Bach)": pages 296-297
Keywords: Bach, Johann Sebastian, -- 1685-1750 -- Criticism and interpretation.; Bach, Johann Sebastian, -- 1685-1750; Bach, Johann Sebastian -- 1685-1750; Bach, Johann Sebastian, -- 1685-1750.; Bach, Johann Sebastian.; Counterpoint -- Textbooks.; Musical analysis -- Music collections.; Analyse musicale -- Anthologies.; MUSIC -- Instruction & Study -- Theory.; Counterpoint; Musical analysis; Kontrapunkt; Contraponto.; Música -- Alemanha.; Electronic books.; Collections; Criticism, interpretation, etc.; Textbooks; Textbooks.